Chapter Signorie e poteri sovralocali nell’Italia centrale. Stato della Chiesa, Toscana e Sardegna - Lattanzio, Federico (Firenze University Press, 2023)
The essay analyses the political relations between rural lordships and supralocal powers in the fourteenth and fifteenth centuries central Italy, on the base of researches carried out during the 2015 project PRIN. The areas considered are the territories of the Papal State, Tuscany and Sardinia. The essay proceeds by territorial frameworks, with the aim of bringing out the different peculiarities of each area and the most relevant common phenomena regarding the relational dynamics between the secular or ecclesiastical domain spaces and the higher powers, with particular reference to the Papacy, to the cities and sovereigns (as in the case of the Aragon Crown in the Sardinian context).